Growth promotion in broilers by both oxytetracycline and Macleaya cordata extract is based on their anti-inflammatory properties. Issue 7 (14th October 2014) - Khadem, Alireza; Soler, Laura; Everaert, Nadia; Niewold, Theo A.
<x content-type="archive" xml:space="preserve">Abstract</x> The non-antibiotic anti-inflammatory theory of antimicrobial growth promoters (AGP) predicts that alternatives can be selected by simple in vitro tests. In vitro, the known AGP oxytetracycline (OTC) and a Macleaya cordata extract (MCE) had an anti-inflammatory effect with a half-maximal inhibitory concentration of 88 and 132 mg/l, respectively. In vivo, chickens received three different concentrations of MCE in drinking-water, OTC in feed and a control. Body weight (BW), feed intake (FI) and gain:feed (G:F) ratio were determined on days 14, 21 and 35. On day 35, body composition was determined. Plasma α1-acid glycoprotein (α1-AG) concentration was measured on days 21 and 35, and the expression of several jejunal inflammatory genes was determined on day 35. OTC-fed chickens showed a significantly higher BW, FI and G:F ratio compared with the control group at all time points. MCE had a significant linear effect on BW on days 21 and 35, and the G:F ratio was improved only over the whole period, whereas FI was not different. Only MCE but not OTC decreased the percentage of abdominal fat. Plasma α1-AG concentration increased from day 21 to 35, with the values being lower in the treatment groups. Both OTC and MCE significantly reduced the jejunal mucosal expression of inducible NO synthase. For most parameters measured, there was a clear linear dose–response to treatment with MCE. In conclusion, the results are consistent with the anti-inflammatory theory of growth promotion in production animals.